Public Health Campaign Program as a Preventive Measure for Stunting in Donorejo Village, Secang District, Magelang Regency - Dwihantoro, Prihatin; Amirudin, Ahmad; Maulana, Rizky Akbar; Indrastoto, Bagaskoro Kusumo; Rafsanjani, Sherlya; Maharani, Devi (Prosiding University Research Colloquium, 2023)
Donorejo is a village located in Secang sub-district, Magelang district. During the observation and interview process with the village, there were 12 children with stunting problems. One of the stunting factors in Donorejo Village is the lack of parental knowledge about nutrition. Therefore, the PPMT activity program implemented includes a nutrition improvement program for stunting children. In addition, the training program on how to make additional food for stunted children The mentoring program is also carried out in providing play therapy for stunted children. Partners in running this program include the village government, youth organization, PKK, cadres, and the local community. The purpose of this activity is to increase knowledge and competence to Donorejo Village community groups related to stunting. With this PPMT program, it is expected to be a preventive effort to prevent and reduce stunting problems in Donorejo village.